An introduction to plant phylogenomics with a focus on palms. (18th March 2016) - Barrett, Craig F.; Bacon, Christine D.; Antonelli, Alexandre; Cano, Ángela; Hofmann, Tobias
Abstract : Phylogenomics refers to the use of phylogenetic trees to interpret gene function and genome evolution and to the use of genome‐scale data to build phylogenetic trees. The field of phylogenomics has advanced rapidly in the past decade due to the now widespread availability of next generation sequencing technologies, which themselves continue to change at a rapid pace and drive down the cost of sequencing per base pair. In this review, we discuss genomic resources available to palm biologists in the form of complete genomes (plastid, mitochondrial, nuclear) and sequenced transcriptomes, all of which can be leveraged to study non‐model palm taxa. We also discuss various approaches to generating phylogenomic data in palms, such as next‐generation sequencing technologies and methodological approaches that allow acquisition of large volumes of biologically and phylogenetically meaningful data without the need to sequence entire genomes (e.g. genome skimming, RAD‐seq, targeted sequence capture). This review was designed for those unfamiliar with phylogenomics and associated methods, but who are interested in engaging in phylogenomics research. We discuss several considerations required for designing phylogenetic projects using genomic data, such as available computing capabilities and level of bioinformatics expertise. We then review some recent, empirical examples of palm phylogenomic studies and how they are shaping the future of palm systematics and evolutionary biology.